Two new species of the genus Anthroherpon Reitter, 1889 from northern Montenegro with notes on the “A. ganglbaueri” species group (Coleoptera: Leiodidae: Leptodirini) - Njunjić, Iva; Perreau, Michel; Pavićević, Dragan (Zootaxa, 2015)
Two new species of Anthroherpon belonging to the “ganglbaueri” species group are described from northern Montenegro: Anthroherpon sinjajevina n. sp. and Anthroherpon cecai n. sp. Based on morphological investigations of other species of this group, we elevate A. udrzali Giachino & Vailati from subspecies to species rank, and suggest the synonymy of A. brckoensis Giachino & Guéorguiev with A ganglbaueri alticola Knirsch. An identification key of the ganglbaueri species group (sensu Guéorguiev, 1990) is given and the distributions of species and subspecies are mapped and discussed.